GATS and International Trade in Health Services: Impact and Regulations - Bakhouya Driss (Faculty of Law, Hasanuddin University, 2017)
This article is interested in studying the impact of trade agreements on the quality of health services, and the statement of the role of the Ministry of Health to protect the quality of these services. The problems that arise in this study; how the application of GATT on trade in health, and services? This article also includes the impact of international trade agreements on the issue of attracting foreign investments in the field of health, and to clarify the government's ability to maintain the health and political, and the capacity of national health products to compete with foreign products. As pointed out repeatedly in this paper, it is too early to make definitive conclusions regarding the impact of GATS, or the liberalization of trade, in the health sector. Nevertheless, we conclude that although so far only a few countries where trade in health services has a major role, trading as it does –which is not based on the GATS or GATS commitments– and appears to be increasing, GATS agreement provides a framework for international trade in services, including health services, but the actual content and obligations are determined in large part by the national government.